PHENOLIC POTENTIAL DETERMINATION AND YEASTS IDENTIFICATION WITH SIGNIFICANT LEAVENS IN ISABELLA GRAPE (Vitis labrusca) FROM VILLA DEL ROSARIO (Norte de Santander) FOR WINE MAKING - HERNANDEZ, José D.; TRUJILLO, Yanine Y.; DURAN Osorio, Daniel Salvador (Vitae, 2011)
The Isabella grape (Vitis labrusca) is a red variety that has been optimally adapted to the edafoclimatic conditions in the region of Villa del Rosario (Norte de Santander) and has been accepted also in local markets. Currently, the grape is eaten fresh and its potential for winemaking is unknown. Therefore, the purpose of this study was to establish the phenolic potential and identify important yeasts of this kind of grape for winemaking. To this end, berries taken from two consecutive vintages were analyzed. Parameters analyzed were density, soluble solids, pH, acidity and total and removable phenolic potential. The yeasts were identified morphologically and biochemically. The results of the physicochemical parameters of the two vintages were averaged and compared with results for grapes from Valle del Cauca. The results indicated that the berries of the two regions were similar in physical characteristics but significantly different in terms of chemical composition. The total phenolic potential was higher in grapes from Valle del Cauca, while removable was similar in the two regions. Five yeast species: Kloeckera apiculata, Criptococcus laurentii, Candida guillermondii, Candida novergensis y Rhodotorula glutinis were microbiologically isolated and identified.